ANALISIS YURIDIS TENTANG TANGGUNG JAWAB PENGURUSAN HARTA ORANG HILANG MENURUT HUKUM ISLAM ( STUDI PENETAPAN NOMOR 137/PDT.P/2013/MS-BND) - IKA LESTARI (PREMISE LAW JURNAL, 2016)
Mafqud is a missing person who is not known whether he is still alive or dead. In the Islamic fiqh, determining the status of mafqud is very important since it is related to many aspects, and one of them is inheritance law. Meanwhile, the testator, of course, needs to know whether his heir is really dead because it is one of the requirements for a mafqud to get inheritance.When a mafqud leaves an inheritance but the heirs are unknown, it will be managed by BAZNAS (the National Tithe Board, particularly in Aceh, it is managed by Baitul Mal . Judge’s legal consideration in determining an heir in the Ruling of Sharia Court No 137/Pdt.P/2013/Ms-Bna, based on the testimony and was validated byGeucihik of Gampong Lampaseh No 470/LPS/MRX/2013 and the petitioner who had Al-Hawasiy lineage (next of kin) with the testator because besides the evidence, determining an heir can be seen from the requirements for being an heir which one of them is the death of a person (testator), either in reality or in legality (for example, he is considered to be dead). In determining the fourth biological child dies because of earthquake and tsunami, the judge , in his legal consideration based on the Death Certificate No 12/IV/LPS/MRX/2013.